(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Recruitment of desired employees in Latvia becomes increasingly challenging. Besides negative demography signals, competition between employers for talent is part of the tight job market. All of this and more is challenging for the businesses to effectively attract employees. Employer branding and recruitment marketing are widely known approaches used by businesses to fulfil their needs and speed up application quantities as well as promote employer attractiveness. Nevertheless, there is a lack of research discussing what effects external HR marketing brings to the labour market. The main task of this study is to analyse the recruitment marketing impact and determine how should recruitment marketing be evaluated. To achieve the goal, a literature review was performed and quantitative data from a survey were collected. The review of existing literature reflects the main factors that should be considered when evaluating recruitment. Additionally, attitudes shared by job seekers regarding recruitment marketing and expectations from employers were collected. The results of the survey showed that the recruitment marketing message can cause bias and encourages individuals to make biased decisions. This research provides a base for future studies by raising several questions – e.g., if the impact of recruitment marketing rises efficiency in the long term and if biases could be beneficial from a brand and an employee perspective, or they become less beneficial. Additionally, no research has considered whether the bias is increasing recruitment sustainability. Further research should be done to understand in what cases employer brand does not bring value to organizational image.